Design and Development of a Pico Hydro Turbine for Small Scale Power Generation System - Ismail F.B.; Mohammed T.S.; Du-Wei D.Y.; Mahdi M.N. (American Institute of Physics Inc., 2024)
The prospective for run-of-river energy harvesting is potentially fruitful and beneficial to rural communities. In this work, the constant flow is harvested by converting kinetic energy into electricity. The necessary parts are the turbine, canal, connecting shaft, and a generator. Critical parts are made from stainless steel whereby all of them had a safety factor of more than 2.0. The total cost for this project would be recouped in 2.1 months with the current national tariffs and operating round the clock. This paper describes the design as well as development of Pico hydropower, which offers a cost-effective, reliable and efficient alternative power source, and handy at remote locations. Static and flow analyses are validated and related to the findings presented in this paper. A proof of concept in the shape of a 30% scale model was constructed out of 3D printed PLA, which differs from the proposed full-scale model of various grades of metal. The results of the scale model testing are in line with other researchers and within the behavior of these components. For a flow rate of (0.1704 m3/s, the calculated power output of the system is (2005.95 watts). On-site hydropower generation is a viable concept that can further be adopted by rural communities, especially with the proposed cost reductions compared to other competing systems. 2023 American Institute of Physics Inc.. All rights reserved.